CODE GLOSSES OF METADISCOURSE IN STUDENTS’ ACADEMIC PRESENTATION - Eva Nur Mazidah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
Academic presentation is one of obligatory task for university students. As they present their academic presentation, composing and organizing their ideas are necessary to make their audience understand what they present. Code glosses as a part of metadiscourse function ‘to signal the restatement of ideational information’ (Hyland, 2005). Nineteen presenters delivered their academic presentation. Their presentations were then transcribed to analyze code glosses applied by the presenters when delivering their academic presentation. These markers are applied to elaborate, modify, define, exemplify or rephrase an intended idea or a concept to readers. The results show that there are 214 markers found indicating that students apply the markers to better modify or elaborate their ideas during their presentation.